1997
DOI: 10.1002/(sici)1097-0215(19970317)70:6<631::aid-ijc1>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

HLA class-I-restricted and tumor-specific CTL in tumor-infiltrating lymphocytes of patients with gastric cancer

Abstract: Immune recognition of human cancers except melanoma is not well understood at either the cellular or the molecular level. We demonstrate in this study the existence of HLA class-I-restricted and tumor-specific CTL in IL-2-activated TIL (tumor-infiltrating lymphocytes) of all 4 gastric cancer patients tested. We established HLA A2-restricted and adenocarcinoma-specific CTL in 2 HLA A0201 1 patients, and HLA A2402-restricted CTL recognizing both adenocarcinoma and squamous-cell carcinomas (SCC) in the 2 remainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The HLA-A haplotype of the patient was HLA-A2/A24, as described in "Materials and Methods." Interestingly, however, A110L expressed no HLA-A2 on the cell surface as judged from the flow cytometry analysis, although EBV-B from the patient expressed HLA-A2, as reported by Hoshino et al 19) in other cancer cell lines. Allele-specific deletion of HLA-A2 of A110L was confirmed by genotypic examination (Table II).…”
Section: Resultssupporting
confidence: 59%
“…The HLA-A haplotype of the patient was HLA-A2/A24, as described in "Materials and Methods." Interestingly, however, A110L expressed no HLA-A2 on the cell surface as judged from the flow cytometry analysis, although EBV-B from the patient expressed HLA-A2, as reported by Hoshino et al 19) in other cancer cell lines. Allele-specific deletion of HLA-A2 of A110L was confirmed by genotypic examination (Table II).…”
Section: Resultssupporting
confidence: 59%
“…Five-year survival rate of gastric cancer is lower than 30%, and the current therapeutic methods show little improvement for gastric cancer survival (2). Tumor-specific cytotoxic T cells are present in gastric cancer tissue, but are unable to contain tumors because of poor immune responses in the tumor microenvironment (3). Reversing this effect would be a potential therapeutic approach to enhance the effectiveness of current treatments.…”
Section: Introductionmentioning
confidence: 99%
“…2 We and others reported that MHC class I-restricted cytotoxic-T lymphocytes (CTLs) from gastric-cancer patients can react specifically against autologous tumor cells. [3][4][5][6] Adoptive immunotherapy based on gastric cancer-specific CTLs, or vaccinations based on the MHC class I-associated tumor antigens that they recognize, represent alternative therapeutic approaches. The presence of tumor-associated antigens recognized by gastric-cancer-specific CTLs restricted by HLA-A31 6 or HLA-A2.1 molecules 4 has been demonstrated, although the nature of these antigens has not been defined.…”
mentioning
confidence: 99%